2020
DOI: 10.1021/acsami.9b21841
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Surfaces Interaction with Proteins, Bacteria, Mammalian Cells, and Blood Constituents: The Impact of Graphene Platelet Oxidation and Thickness

Abstract: Graphene-based materials (GBMs) have been increasingly explored for biomedical applications. However, interaction between GBMs-integrating surfaces and bacteria, mammalian cells, and blood components, that is, the major biological systems in our body, is still poorly understood. In this study, we systematically explore the features of GBMs that most strongly impact the interactions of GBMs films with plasma proteins and biological systems. Films produced by vacuum filtration of GBMs with different oxidation de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…Both the FLGO and GO composites showed hydrophilicity comparable to that of the neat PEG hydrogels with a water contact angle <20 • . It has been reported that the FLGO and GO films produced by vacuum filtration present water contact angles of 42 • and 33 • , respectively [53]. The maintenance of high hydrophilicity in composite hydrogels may be explained by the fact that GBM are encapsulated within the hydrogel matrix, with almost no sheets or sharp edges exposed at the surface (as shown in SEM images).…”
Section: Discussionmentioning
confidence: 96%
“…Both the FLGO and GO composites showed hydrophilicity comparable to that of the neat PEG hydrogels with a water contact angle <20 • . It has been reported that the FLGO and GO films produced by vacuum filtration present water contact angles of 42 • and 33 • , respectively [53]. The maintenance of high hydrophilicity in composite hydrogels may be explained by the fact that GBM are encapsulated within the hydrogel matrix, with almost no sheets or sharp edges exposed at the surface (as shown in SEM images).…”
Section: Discussionmentioning
confidence: 96%
“…Graphenic materials are capable of adsorbing proteins and ions onto their surface through van der Waals, π-π, electrostatic, and hydrogen bonding interactions. [50][51][52] Zeta potential of our FGMs in bacterial culture media (LB Miller and Trypticase Soy broth) demonstrates this phenomenon: the zeta potential of all FGMs becomes indiscriminately negative in media, which is likely due to adsorption of media components…”
Section: Characterization Of Fgm Functionalizationmentioning
confidence: 74%
“…Quantification of the green and red fluorescence reveals that CG has significantly fewer total cells (Green FL + Red FL) than either of the PLL n -G materials ( p < 0.05, "#" symbol). Further, PLL 6 -G fosters more live cells (Green FL) than PLL 50…”
Section: Papermentioning
confidence: 99%
“…Therefore, graphene surfaces can be produced with different wettability and roughness by controlling the degree of oxidation. Protein adsorption can be predicted and modulated by the intertwining of these factors [ 52 ]. As an example, single-layer graphene oxide (GO) and few-layer graphene oxide can form smooth hydrophilic and anti-fouling surfaces, which significantly resisted unspecific protein adsorption.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%